SPEED CONTROL OF DC MOTOR ON LOAD USING FUZZY LOGIC CONTROLLER (A CASE STUDY OF EMERGENCY LUBE OIL PUMP MOTOR OF H25 HITACHI TURBINE GENERATOR) (Nigerian Journal of Technology, 2017)
This paper presents the development of a fuzzy logic controller for the driver DC motor in the lube oil system of the H25 Hitachi gas turbine generator. The turbine generator is required to run at an operating pressure of 1.5bar with the low and the high pressure trip points being 0.78 bar and 1.9 bar respectively. However, the driver DC motor speed drifted from the desired speed of 1450 revolutions per minutes (rpm) to as low as 1414 rpm. It is against this backdrop, that this project work was envisaged to design a controller capable of controlling the speed of the DC motor in order to achieve the desired speed rating of 1450 rpm. In modelling the motor, the transfer function method was used to develop a linear approximation to the actual motor. After computing the total inertia of the motor shaft, the motor model was simulated for the speed response in MATLAB and Simulink environment, and the response showed that the motor attained an actual maximum speed of 1414 rpm at settling time of 0.3 seconds.  Based on expert knowledge of the lube oil system, a fuzzy logic controller was designed and this resulted in the issuance of a control action to correct the actual speed of the motor from 1414 rpm to the desired speed of 1450 rpm.  http://dx.doi.org/10.4314/njt.v36i3.29